The Effect of Enduring Service Intensifiers, Perceived Service Alternatives, and Self-Perceived Roles on the Level of Customer Satisfaction Using the Importance Performance Analysis Method (Case Study of Bank Sumut Syariah KC. Medan) - Herlina Herlina; Tuti Anggraini; Muhammad Syukri Albani Nasution (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the relationship and influence of Enduring Service Intensifiers, Perceived Service Alternatives, Self-Perceived Roles on the Level of Consumer Satisfaction using the importance performance analysis method (case study of Bank Sumut Syariah Kc. Medan). The type of research used in this study is quantitative research. The object of this research was conducted at Bank Sumut Syariah branch office Jl Imam Bonjol Medan. The population used in this study were Bank Sumut Syariah customers who saved at the bank in the first quarter of 2023, as many as 2,340 people. The sample in this study was 96 people. Data collection techniques used multiple linear analysis with the help of the SPSS program version 23.0. Based on the results of the partial hypothesis test (t-test), it shows that the variables Enduring Service Intensifiers, Perceived Service Alternatives, Self Perceives Roles have a significance value of <0.05, which means that the variables Enduring Service Intensifiers, Perceived Service Alternatives, Self Perceives Roles have a positive and significant influence on increasing consumer satisfaction, so that the hypothesis in this study is accepted.